2016
DOI: 10.1007/s12035-016-0145-3
|View full text |Cite|
|
Sign up to set email alerts
|

Tauroursodeoxycholic Acid Protects Against Mitochondrial Dysfunction and Cell Death via Mitophagy in Human Neuroblastoma Cells

Abstract: Mitochondrial dysfunction has been deeply implicated in the pathogenesis of several neurodegenerative diseases. Thus, to keep a healthy mitochondrial population, a balanced mitochondrial turnover must be achieved. Tauroursodeoxycholic acid (TUDCA) is neuroprotective in various neurodegenerative disease models; however, the mechanisms involved are still incompletely characterized. In this study, we investigated the neuroprotective role of TUDCA against mitochondrial damage triggered by the mitochondrial uncoupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Currently, it is not clear why such a higher concentration of TUDCA is required to observe an effect in embryos. One possibility is that IVM oocytes may cause more ER stress or additional impairment to the mitochondria after IVF, as TUDCA treatment also protects against mitochondrial dysfunction [ 19 ]. Thus, the concentration of TUDCA used for treatment of IVM oocytes should be optimized differently from in vivo matured oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not clear why such a higher concentration of TUDCA is required to observe an effect in embryos. One possibility is that IVM oocytes may cause more ER stress or additional impairment to the mitochondria after IVF, as TUDCA treatment also protects against mitochondrial dysfunction [ 19 ]. Thus, the concentration of TUDCA used for treatment of IVM oocytes should be optimized differently from in vivo matured oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several markers of apoptosis were attenuated including caspase 3 activation and nuclear fragmentation. Other, subsequent studies using TUDCA, the taurine conjugate of UDCA have shown very similar effects in the SHSY5Y model after CCCP treatment ; MMP and ROS were again normalised after TUDCA treatment. Mitochondrial dysfunction has been noted as a major phenotype in several Caenorhabditis elegans genetic models of PD induced by expressing or deleting alpha‐synuclein , parkin or DJ1 .…”
Section: Targeting Mitochondria For Neuroprotection In Parkinson's DImentioning
confidence: 68%
“…The therapeutic effect resulted in preservation of function and morphology of photoreceptor cells in retina [ 9 , 14 , 15 , 16 , 17 ]. Among the proposed mechanism of cytoprotective action of TUDCA we may include the inhibition of classic apoptosis pathways [ 18 ], decrease of endoplasmic reticulum stress and protein aggregation [ 19 , 20 ], stabilization of mitochondrial membranes [ 21 , 22 ], prevention of DNA damage [ 23 ], and stimulation of antioxidant mechanisms through activation of the nrf2 transcription factor [ 24 , 25 ]. The most recent data demonstrated that if ARPE–19 cells were exposed to H 2 O 2 in the presence of TUDCA, the bile acid increased cells viability and enhanced their antioxidant capacity by increasing the level of glutathione and upregulating the expression of antioxidant genes [ 25 ].…”
Section: Introductionmentioning
confidence: 99%